Single functional index quantile regression for independent functional data under right-censoring - Hamri, Mohamed Mehdi; Mekki, Sanaà Dounya; Rabhi, Abbes; Kadiri, Nadia (Regresja kwantylowa pojedynczego wskaźnika funkcjonalnego dla niezależnych danych funkcjonalnych z cenzurowaniem prawostronnym, 2022)
The main objective of this paper was to estimate non-parametrically the quantiles of a conditional distribution based on the single-index model in the censorship model when the sample is considered as independent and identically distributed (i.i.d.) random variables. First of all, a kernel type estimator for the conditional cumulative distribution function (cond-cdf) is introduced. Then the paper gives an estimation of the quantiles by inverting this estimated cond-cdf, the asymptotic properties are stated when the observations are linked with a single-index structure. Finally, a simulation study was carried out to evaluate the performance of this estimate.
Econometrics = Ekonometria, 2022, Vol. 26, No. 1, s. 31-62
Keywords: censored data; functional data; kernel estimation; normality; non-parametric estimation; small ball probability; dane cenzurowane; estymator jądrowy; normalność; estymacja nieparametryczna; prawdopodobieństwo small ball